Kepemimpinan Instruksional Kepala Sekolah Dalam Membangun Budaya Sekolah Adiwiyata Pada Sekolah Baru - Aris Broto; Muhammad Zuhaery; Dian Hidayati (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study employed a qualitative approach using a case study design at SMP Negeri 28 Balikpapan. The participants consisted of three informants, including one principal and two teachers, who were selected through purposive sampling based on their involvement in the implementation of the Adiwiyata School program. Data were collected through in-depth interviews and observations and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings identified three major dimensions of instructional leadership in fostering an Adiwiyata School culture: the management of environment-based learning programs, the development of a supportive school climate, and the transformation of school culture through the strengthening of vision, role modeling, habituation, and active participation of all school members. These three dimensions functioned in an integrated manner to internalize environmental values and develop them into a sustainable school culture. The study demonstrates that, within the context of a newly established school, instructional leadership not only enhances the quality of teaching and learning but also serves as an integrative mechanism that aligns the school's vision, instructional management, and school climate to cultivate a sustainable Adiwiyata School culture.